Impact of early-onset preeclampsia on feeding tolerance and growth of very low birth weight infants during hospitalization - Pelícia, Simone Manso de Carvalho [UNESP]; Fekete, Saskia Maria Wiegerinck [UNESP]; Corrente, Jose Eduardo [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP] (FapUNIFESP (SciELO), 2022)
OBJECTIVE: The provision of adequate enteral nutrition to preterm infants is a great challenge, and preeclampsia (PE) may have a detrimental effect on the safety of nutrition supply. This study aims to investigate the influence of early-onset PE on preterm infants' enteral feeding tolerance and growth during hospitalization. METHODS: This is a prospective study with 55 preterm infants <34 weeks born to PE mothers matched by gestational age with 55 preterm infants born to normotensive mothers from 2013 to 2016. We evaluated maternal, gestational, and neonatal clinical data. The outcomes were feeding intolerance and growth during hospitalization. Comparison between groups was performed by Student's t-test or Mann-Whitney U test, chi-square test, or Fisher's exact test. Multiple logistic regression was used to investigate whether PE was an independent risk factor for feeding intolerance. RESULTS: The mean gestational age was 30 weeks. Preterm infants of mothers with PE had lower birth weight and were smaller at discharge. Feeding intolerance was frequent, but necrotizing enterocolitis was rare in this sample (PE=4% vs. control=2%) with no difference between groups. Preterm infants of mothers with PE had worse growth outcomes; however, PE was not an independent risk factor for feeding intolerance. The increase in gestational age was a protective factor, and being born small for gestational age (SGA) increased the risk of feeding intolerance by six times. CONCLUSIONS: Preterm infants of mothers with early-onset PE were more likely to be born SGA and had a worse growth trajectory during hospitalization. In adjusted analyses, however, low gestational age and SGA were independent predictors of feeding intolerance.